The case for stronger scrutiny of the deductibility of crypto losses - OOI, Vincent (Institutional Knowledge at Singapore Management University, 2024)
Crypto losses have the potential to adversely impact the tax base, particularly if they are deducted against income from other profitable sources. There is a key question of fairness as to whether crypto losses should be cross-subsidised by income from other sources that may have nothing to do with cryptoassets at all. This article argues for stronger scrutiny of the deductibility of crypto losses at the stage of determining whether such losses can be set off against income from other sources or at the stage of the shifting of the losses across time and between companies. It explains why crypto losses are of particular concern to tax systems and considers how safeguards can be put in place at both stages to safeguard the tax base. In particular, it suggests that specific crypto legislation should be enacted in order to impose a loose “source matching” requirement on crypto losses. Crypto losses from the carrying on of a trade or business should only be deductible against crypto income. That said, there is probably no need to strictly require that the source of the crypto losses must exactly match the source of the crypto income which is sought to be deducted.